A self‐reinforced activatable photosensitizer prodrug enabling synergistic photodynamic and chemotherapy - Daipeng Huang; Jikai Yin; Yang Zou; Haiqiao Huang; Saran Long; Wen Sun; Jianjun Du; Jiangli Fan; Xiaojun Peng (Smart Molecules, 2024)
Abstract As a novel drug development paradigm, selective activation of prodrugs provides the potential for precise tumor chemotherapy, thereby presenting an opportunity for advancing cancer treatment. The combination of photodynamic therapy (PDT) and prodrug can enhance the therapeutic efficacy while simultaneously enabling real‐time monitoring of drug distribution and release. However, the tumor hypoxia microenvironment and the frequent high‐dose administration of prodrugs significantly impede therapeutic efficacy and escalate treatment‐related risks. Herein, a tumor microenvironment‐specific release prodrug is constructed, termed NBS‐2S‐5FU. Under the influence of glutathione (GSH), NBS‐2S‐5FU undergoes activation, leading to the release of photosensitizer NBS and chemotherapeutic agent 5‐FU derivatives. Under irradiation, NBS produces sufficient superoxide radical (O2−•) while 5‐FU derivatives inhibit DNA biosynthesis, thereby effectively suppressing tumor growth at low doses. Subsequent in vivo studies utilizing NBS‐2S‐5FU liposomes exhibit outstanding anti‐cancer effectiveness. This study highlights a promising direction for advancing combined prodrugs that integrate PDT and chemotherapy.